Machine Learning Applications: Emerging Trends - Das, Rik; Bhattacharyya, Siddhartha; Nandy, Sudarshan (De Gruyter Frontiers in Computational Intelligence, 2020)
The publication is attempted to address emerging trends in machine learning applications.Recent trends in information identification have identified huge scope in applying machine learning techniques for gaining meaningful insights.Random growth of unstructured data poses new research challenges to handle this huge source of information.